Logistics performance and export variety: Evidence from Turkey - Ünal Töngür; Kemal Türkcan; Seda Ekmen-Özçelik (Central Bank Review (CBR), 2020)
This study examines the effects of logistics infrastructure on export variety, as measured by the extensive margin. Using finely disaggregated exports data for Turkey's trade with 174 countries over the period 2007-2017, we decompose gross export flows into the extensive and intensive margins of Turkish exports utilizing the method developed by Hummels and Klenow (2005). Gravity estimates suggest that logistics infrastructure positively influences export values and has a greater impact on the extensive margin than the intensive margin. Our empirical analysis further suggests that Turkish exporters are more sensitive to changes in local market logistics conditions than to those of their trade partners. These findings are robust to a variety of alternative measures and estimation methods.
Keywords: F13; F14; H54; O18; O24; 330; Trade facilitation; Logistic performance; Export margins; Export variety; Turkey